Prevalence and Socio Demographic Characteristics of Disability in Older Adults in China Retrospective Study: A Literature Review - Hamidah Retno Wardani (Lembaga Penelitian dan Pengabdian Masyarakat Program Studi DIII Keperawatan Universitas Bondowoso, 2020)
Introduction: Illness, injury and aging are the main causes of disability in the elderly, elderly people with disabilities experience economic and health stresses, and may also experience mental and psychological distress, and other life difficulties. The aim of this study was to clarify the prevalence and socio-demographic characteristics of disability in the elderly. Elderly care is a concern of the whole community. Method: The research method used is a retrospective study, namely research (survey) where the design is used to provide information related to the prevalence, distribution and relationships between variables in a population. Result: The bivariate relationship between the level of disability in the elderly according to sex, area, age, social status and in different cities was analyzedwith P value <0.05 was considered statistically significant. The disability rate in adults is 7.0%. Disability rates were significantly higher in women than men, significantly higher in rural areas than urban areas, and higher in northern China than southern China. The urban disability rate ranges from 5.7% to 1.2%. The difference is statistically significant, with Beijing having the highest disability rate and Shanghai the lowest. Defects increase with age. Conclusion: This study shows that the rate of disability among elderly people in northern China is significantly higher than in southern China